Performance Evaluation of Shell and Tube Heat Exchanger With Capacity of 100,000 Btu/Day in Cilacap - Aqilah, Griselda Ivonne; Nugroho, Budi Sulistiyo; Alvino, Nimrod (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
A heat exchanger (HE) is a heat exchanger that has a vital role in the oil and gas processing industry. Especially in the Fuel Oil Complex I (FOC I) unit, which is tasked with separating crude petroleum into fractions such as LPG, light naphtha, heavy naphtha, kerosene, Light Gas Oil (LGO), Heavy Gas Oil (HGO) and long residue. The continuous use of heat exchangers will cause fouling over time. The Cilacap oil and gas processing industry uses a shell and tube type heat exchanger because it has cost, fabrication, and work advantages. The evaluation results of the comparison of the fouling factor (Rd) and pressure drop values on the design data and actual data on 1 June - 30 July 2024 show that the actual fouling factor (Rd) value is greater than the design fouling factor (Rd) value. While the actual ∆P pressure drop shell side and tube side values are smaller than the design pressure drop values because the actual flow rate is much smaller than the design data flow rate. The recommendation is periodic evaluation and cleaning of accumulated dirt, mud, and scale found on the shell and tube walls to maintain heat exchanger performance.